Social impact of soybean in Nigerias southern Guinea savanna - Sanginga, P.; Adesina, A.A.; Manyong, Victor M.; Otite, O.; Dashiell, Kenton E. (1999)
Most impact studies of agricultural technologies use economic models, with little direct attention being paid to the actual impact on the lives of resource-poor farmers. This paper uses a social impact assessment (SIA) framework to examine the level of adoption and impact of soybean on farm households in Nigeria based on a survey of 203households in Benue State. The results show that the status of soybean has changed from a traditionally male controlled minor export crop, to one of the most important crops cultivated by the majority of male and female farmers. More women have become involved in soybean production as improved varieties and household utilization technologies have become readily available. The new varieties have been widely adopted, beginning with 9% of farmers in 1989 reaching over 75% in 1997, and these now occupy about 30% of the total soybean land area. Analysis conducted with a Tobit model showed that farmers' socioeconomic characteristics and farmers' assessment of the attributes of improved varieties were both important in explaining their adoption behavior. The adoption of soybean has had a clear positive impact on household income generation and distribution, material welfare, human capital development, gender relations, resource use, social equity, and other social processes in the community. Many innovations in soybean utilization have been adopted, to the extent that soybean has become a staple food. The results further showed that the nutritional status of children was significantly better in soybean producing/using households than in those that did not use soybean. A multivariate analysis of the nutritional status of children showed that soybean consumption, income earned from soybean, and women's production of soybean had significant positive impacts on both the short-and long-term nutritional status indices. The results of this study provide a strong case for the promotion of soybean as a cheap solution for malnutrition and a means of poverty alleviation for poor people.